Influence of C-Defects on enhanced nucleation of AL IN ON SI (100) : 2x1 a kinetic Monte Carlo study - Albia, Jason Rayala (National Institute of Physics, College of Science, University of the Philippines Diliman, 2013)
The impact of C-defects on enhanced nucleation and subsequent one-dimensional (ID) growth of Al and In nanowires on Si(100):2x1 at different temperatures (150K- 500K) was investigated via kinetic Monte Carlo(KMC) simulations of a suitable atomistic model. The average island density and average island size at various defect densities as temperature increases were determined. Consistent with experimental and theoretical studies, results revealed that C-defects serve as efficient nucleation sites for diffusing Al and In adatom. The disparity between nucleation and growth behavior of these two systems can be attributed to weaker In-In and stronger In-C-defect binding energy compared to Al-Al and Al-C-defect binding energy, respectively.